Моніторинг вібраційного стану агрегатів гідроелектростанцій - Філіпович, Юрій; Каграманян, Кароліна; Боднарчук, Андрій (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
Моніторинг обладнання гідроелектростанції (ГЕС) є важливою частиною її ефективної експлуатації та обслуговування. Цей процес включає в себе систематичне спостереження, збір та аналіз даних про стан елементів ГЕС, щоб вчасно виявляти можливі проблеми, запобігати відмовам обладнання та збільшити робочу продуктивність. <pre id="tw-target-text" class="tw-data-text tw-text-large tw-ta" dir="ltr" tabindex="-1" role="text" data-placeholder="Переклад" data-ved="2ahUKEwit-4Xvl4WQAxWCRvEDHSG7I_sQ3ewLegQICxAV" aria-label="Перекладений текст: Monitoring of hydroelectric power plant (HPP) equipment is an important part of its effective operation and maintenance. This process involves systematic observation, collection and analysis of data on the condition of HPP elements in order to timely detect possible problems, prevent equipment failures and increase operational productivity.">Monitoring of hydroelectric power plant (HPP) equipment is an important part of its effective operation and maintenance. This process involves systematic observation, collection and analysis of data on the condition of HPP elements in order to timely detect possible problems, prevent equipment failures and increase operational productivity.